Gapena and the Cape Malays: Initiating connections, constructing images - Muhammed Haron, (Universiti Kebangsaan Malaysia, 2005)
This article intends to demonstrate how cultural organizations, such as Gapena under the leadership of Ismail Hussein, have been among non-state actors that have been active in international relations. It also highlights the three variables, namely identity, culture and religion, which inform the activities of these non-state actors. In addition, it wants to reflect upon the religio-cultural relationship cemented and strengthened between Gapena and South Africa’s Cape Malays and it also shares thoughts on how Ismail Hussein played a pivotal role in this. Prior to this, the paper takes into account the debates surrounding the notion of ‘Malayness’ within the respective communities and offers a comparative view. Finally, it shows how their identities have been framed and how images were constructed within the respective communities